Realising distributed leadership through measurement for change - Watkins, Jonathan; Muhamedjonova, Nazira; Holding, Penny A. (Frontiers in Public Health, 2023)
Through a systematic reflection on the journey that transformed traditional state-run baby homes in Tajikistan from closed institutions into community-oriented Family and Child Support Centres (FCSC) we reveal key moments of change. This review describes how community consultation with local participants in a development project shifted responsibility and accountability from international to local ownership and how distributed leadership contributes to the decolonisation of social services. Based on these interviews we ask, “How do the innovations of a social development project become a fixed part of normal local social, cultural and political life; and, how do we know when a new normal is self-sustaining at a local level?” This analysis builds on a network-mapping tool previously described in this journal. Our interviews show that each participant has taken a non-linear journey, building on the networks previously described, under the influence of activities and discussions that emerged throughout the project. We consider how a monitoring, evaluation and learning process should be responsive over time to these influences, rather than be set at the start of the project. Using the themes that emerge from participants’ journeys, we apply a ‘measurement for change’ (M4C) approach that integrates Monitoring, Evaluation and Learning (MEL) into decision-making. The journey framework applied represents a systematic application of the M4C approach that gives us insight into where local ownership is responsible for the sustainable management of the intervention, and where continued partnership will further strengthen impact and accountability. The exercise has provided evidence of progress towards decolonisation and of the centring of local priorities in MEL and implementation processes.